PERSONALIA : On the Eightieth Birthday of Valentin Georgievich Dmitriev. (29th November 2016) - Krokhin, O N; Zverev, G M; Gulyaev, Yu V; Kovsh, I B; Shcherbakov, I A; Makarov, V A; Bugaev, A S; Kudryavtsev, N N; Kopylov, S M; Fomichev, A A; Golyaev, Yu D; Rustamov, S R; et al.
Abstract: November 15, 2016 marks the 80th birthday of Valentin Georgievich Dmitriev, a prominent Russian scientist, whose entire life in science was devoted to nonlinear optics and laser gyroscopy.